CLASSICAL PHYSICS PROBLEMS OF THE LATE 19TH CENTURY THE EMERGENCE OF QUANTUM THEORY (American Journal of Pedagogical and Educational Research, 2023)
In the article, the problems of classical physics, the emergence of the quantum theory, the structure of the atom, the linear spectra of recovery and absorption, quantum in the creation of photoelectric effects, which are considered important from a historical, methodological, informative and philosophical point of view, are presented in the article. The importance of mechanics is discussed.